What drives Management Buyout activity across Europe? A panel data analysis - Daley, Philip (2009)
This paper investigates the determinants of Management Buy-out and Buy-in activity across Europe from 1998-2007 and uncovers a number of new and exciting findings to the research area. Using panel data analysis, and consistent with existing research, I find that GDP volume and Liquid Stock Markets are important factors in buyout activity. In addition to this, I find that a higher degree of state control, regulation and labour union power has a detrimental effect on buyout activity. On the other hand, a strong legal and technological environment has a major impact on the value and volume of buyout deals.